2022
DOI: 10.1002/bmc.5374
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tang Luo Ning on diabetic peripheral neuropathy in rats revealed by LC–MS metabolomics approach

Abstract: Diabetic peripheral neuropathy (DPN) is one of the most common complications of diabetes with limited therapies. Tang Luo Ning (TLN), a traditional Chinese medicine compound, has been proved to be effective in the treatment of DPN in clinical and experimental studies. However, the potential metabolic mechanism of TLN for the treatment of DPN is still unclear. Here the therapeutic effect of TLN on DPN was studied, and HPLC‐IT‐TOF/MS was used to explore the metabolic changes related to DPN and to explore the mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…It was concluded that the JMT decoction has obvious protective effects on diabetic peripheral neuropathy rats, and its mechanism may be related to improving the metabolic disorders in peripheral neuropathy rats. Li et al [ 111 ] used the HPLC-IT-TOF/MS technique to study the mechanism of action of Tang Luo Ning (TLN) on high-glucose-induced diabetic peripheral neuropathy, and metabolic pathway analysis was used to explore the effects of DPN and TLN on the metabolism of rats. Metabolomics analysis revealed 14 potential biomarkers (citrate, creatine, fumarate, glycerate, glycine, succinate, etc.)…”
Section: Ms-based Metabolomics In Clinical Cases Of Diabetes-induced ...mentioning
confidence: 99%
“…It was concluded that the JMT decoction has obvious protective effects on diabetic peripheral neuropathy rats, and its mechanism may be related to improving the metabolic disorders in peripheral neuropathy rats. Li et al [ 111 ] used the HPLC-IT-TOF/MS technique to study the mechanism of action of Tang Luo Ning (TLN) on high-glucose-induced diabetic peripheral neuropathy, and metabolic pathway analysis was used to explore the effects of DPN and TLN on the metabolism of rats. Metabolomics analysis revealed 14 potential biomarkers (citrate, creatine, fumarate, glycerate, glycine, succinate, etc.)…”
Section: Ms-based Metabolomics In Clinical Cases Of Diabetes-induced ...mentioning
confidence: 99%
“…[21][22][23] Li et al discovered 14 potential biomarkers of both DPN and Tang Luo Ning treatment by metabolomics analysis. 24 In addition, metabonomics not only contributed to understanding the TCM theory but has also been used to analyze the applications, the mechanisms, and the safety assessment of Chinese herbs. [25][26][27][28] Based on the multi-component, multi-effective, and multi-target characteristics of herbal compounds, the primary aim of this study was to investigate whether Liu-Wei-Luo-Bi (LWLB) granules improve type 2 DPN and the specific mechanism using untargeted metabolomics techniques.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 43 metabolites were identified as potential biomarkers related to the therapeutic effect of LWLB granules. Fifty,4,and 26;23,4,and 22;and 24,1,and 16 biomarkers were discovered in the LW-l, LW-m, and LW-h groups at the 4th, 6th, and 12th weeks, respectively. Five, three, seven, five, and four metabolic pathways were found in MD, Epa, LW-l, LW-m, and LW-h groups, respectively.…”
mentioning
confidence: 97%